(untitled) (Rudarsko-geološko-naftni zbornik, 2020)
In this study, the safe charge per delay (kg) of explosives and Peak Particle Velocity (PPV, mm/s) are recorded for 140 blast events at various distances which relates to the dam and hydropower projects of Karoun III, Masjed – Soleiman, and Siah – Bisheh in Iran. Parameters of Scaled Distance (SD) are estimated carefully. For the prediction of PPV, empirical equations are used. The correlation coefficients resulting from these predictors in diverse sites, are different because of varying conditions in the geomechanical and blasting parameters at each site. Therefore, considering several initial blasts and analysing their results, a suitable relationship has been selected for each case study.